Analisis Nilai Pendidikan Karakter Dalam Tuturan Ferdy Irwandi Dan Bagus Muljadi Dalam Podcast Malaka Project Sebagai Penanaman Karakter Dalam Menyimak Kritis Di Era Digital Pada Siswa - Sri Ulina Beru Ginting; Nazwa Nazhilla; Annisa Sinuraya; Siti Rahayu; Ayu Masdalifah (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to describe the character education values contained in the utterances of Ferry Irwandi and Bagus Muljadi in the Malaka Project podcast and their relevance to fostering students’ critical listening skills in the digital era. The development of digital media has made podcasts one of the communication and learning media closely related to the lives of young generations. Through podcasts, students not only obtain information but also learn to understand, evaluate, and critically analyze the content delivered by speakers. Therefore, the analysis of character education values in digital media is important to support contextual learning that aligns with current developments. This study employed a qualitative approach using a descriptive content analysis method. The data source consisted of utterances from the Malaka Project podcast episode featuring Ferry Irwandi and Bagus Muljadi, accessed through the YouTube platform. Data collection techniques were carried out through listening, note-taking, and transcription methods. The data were analyzed using pragmatic speech act theory and the concept of character education to identify character values contained in the speakers’ utterances. The stages of data analysis included data reduction, data presentation, and conclusion drawing. The findings revealed several dominant character education values in the speakers’ utterances, namely critical thinking, honesty, responsibility, curiosity, and social awareness. The value of critical thinking was reflected in utterances encouraging listeners to verify information and not easily believe news without clear evidence. The value of honesty appeared in the delivery of opinions supported by logical arguments and data. In addition, the utterances in the podcast demonstrated the importance of intellectual responsibility and awareness in using digital media wisely. The findings indicate that podcasts can be utilized as learning media that support character building while also improving students’ critical listening skills in the digital era Keywords: character education, podcast, critical listening skills